Linguistic creativity in the school setting: A case study of Indonesian children’s verbal language play in an international elementary school - Deviyanti, Rafista; Nisa, Khairun (Universitas Lampung, 2024)
The purpose of this qualitative case study was to explore the verbal language play production of two Indonesian children studying at Rainbow Junior International School in Bali. The study aimed to explain how language play functioned as input for the children's English language learning within the natural language environment of the school. Two second-grade students, Didi and Rosie, were observed for 22 days during their interactions with peers and teachers. The findings revealed that the subjects produced a significant amount of language play. The study suggests that providing children with support and exposure to language play can encourage metalinguistic awareness and language growth.Keywords: language play, language acquisition, case study, children